Application of Epoxy Mortar in Anti-erosive Protection of the Spillway on the Xin'anjiang Hydropower Station Plant. (May 2017) - Huang, Hao; Hao, Jutao; Zhao, Bo; Zhao, Xinhua; Li, Meng; Liu, Jiahong; Shao, Weiwei
Abstract: Study on surface protection is an important content of hydropower energy engineering. As a crucial surface-protection material in hydraulic structures, epoxy mortar has been applied in the anti-erosive protection of structures such as tunnels and the spillways of dams. However, its large-scale application is still limited, to some extent, in outdoor environments such as the spillways of dams, as it is greatly affected by natural conditions with the easy occurrence of damages, including cracking, warping, and disengaging. In this paper, we analyze the large-scale application practice of epoxy mortar in the spillway on top of the Xin'anjiang dam plant and present the problems in the application while providing references for the further improvement of surface protection of hydropower project and energy supply.